THE INFLUENCE OF BUDGET TRANSPARENCY ON PUBLIC PARTICIPATION IN REGIONAL FINANCIAL SUPERVISION: A SYSTEMATIC LITERATURE REVIEW - Lilis Karfina AR; Haliah; Nirwana (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This systematic literature review explores the impact of budget transparency on public participation in regional financial supervision. The review highlights the essential role of transparency in promoting accountability, fostering public trust, and enhancing the efficiency of local governance. Public participation, as a key element in the budgeting process, helps to ensure that government expenditures align with the needs and priorities of citizens, thereby improving the effectiveness of financial oversight. The review also addresses the challenges and barriers faced in implementing budget transparency and public participation, such as limited public access to financial information, lack of civic engagement, and political resistance. By synthesizing findings from various studies, the review underscores the significance of fostering a transparent, inclusive environment that encourages active public participation in regional financial management. The study concludes that effective budget transparency, coupled with robust public involvement, is essential for achieving sustainable development and good governance at the regional level.